Urinary neutrophil gelatinase-associated lipocalin (NGAL) as an early marker of acute kidney injury in critically ill multiple trauma patients - Makris, K.; Markou, N.; Evodia, E.; Dimopoulou, E.; Drakopoulos, I.; Ntetsika, K.; Rizos, D.; Baltopoulos, G.; Haliassos, A. (Clinical Chemistry and Laboratory Medicine, 2009)
Background: Neutrophil gelatinase-associated lipocalin (NGAL), an iron-transporting protein rapidly accumulating in the kidney tubules and urine after nephrotoxic and ischemic insults, has been put forward as an early, sensitive, non-invasive biomarker for acute kidney injury (AKI). The aim of this study was to evaluate urinary NGAL levels as a predictor of early AKI (first 5 days after injury) in multi-trauma patients. Methods: We studied multi-trauma adult patients admitted to the intensive care unit of a trauma hospital. Exclusion criteria were a) known cardiac or chronic kidney disease, and b) initial evaluation after more than 24 h had elapsed from injury. Urinary NGAL was measured using an ELISA technique upon admission and at 24 and 48 h. Presence of AKI was defined by the risk injury failure loss and end-stage kidney classification (RIFLE) criteria. Data are reported as median and interquartile range. Results: A total of 31 patients (25 male, 6 female) were studied. NGAL levels at admission were significantly higher among patients who subsequently developed AKI [155.5 (50.5-205.9) ng/mL vs. 8.0 (5.7-17.7) ng/mL, p=0.0000] and these higher levels persisted over the following 2 days. On the basis of receiver-operating characteristic analysis both NGAL and serum creatinine baseline measurements could predict AKI [area under the curve (95% confidence interval) 0.977 (0.823-0.980) and 0.789 (0.556-0.906), respectively], but the area under the curve for NGAL was significantly larger (p=0.024). A cut-off point >25 ng/mL for NGAL had a sensitivity of 0.91 and specificity of 0.95 in predicting AKI. Conclusions: Urinary NGAL can be used from the 1st day of injury as a reliable predictor of early AKI in multi-trauma patients. © 2009 by Walter de Gruyter.
Keywords: Acute kidney injury; Acute renal failure; Multi-trauma patients; Neutrophil gelatinase-associated lipocalin (NGAL)